Standard specification for aluminum-coated steel chain-link fence fabric1 (American Society for Testing and Materials, 2007)
This specification covers aluminum-coated steel chainlink fence fabric, aluminum-coated before weaving. The values stated in inch-pound units are to be regarded as the standard. The values given in parentheses are for information only.